ChemInform Abstract: The Synthesis of 5‐Substituted 1H‐Tetrazoles in Molten Tetrabutylammonium Bromide. Issue 24 (2nd June 2014) - Xie, Aming; Cao, Meiping; Feng, Liandong; Dong, Wei
Abstract Use of molten Bu4NBr allows to carry out the reaction without any additional catalyst or organic solvent.